Stage-Dependent Regulation of Dental Pulp Stem Cell Odontogenic Differentiation by Transforming Growth Factor-β1 - Yu Bai; Xin Liu; Junqing Li; Zhihua Wang; Qian Guo; Min Xiao; Paul R. Cooper; Qing Yu; Wenxi He (Hindawi Limited, 2022)
Transforming growth factor-β1 (TGF-β1) is an important multifunctional cytokine with dual effects on stem cell differentiation. However, the role of TGF-β1 on odontogenic differentiation of dental pulp stem cells (DPSCs) remains to be entirely elucidated. In the present study, we initially investigated the effect of TGF-β1 at a range of concentrations (0.1-5 ng/mL) on the proliferation, cell cycle, and apoptosis of DPSCs. Subsequently, to determine the effect of TGF-β1 on odontogenic differentiation, alkaline phosphatase (ALP) activity and Alizarin Red S (ARS) staining assays at different concentrations and time points were performed. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot analysis were used to determine the levels of odonto-/osteo-genic differentiation-related gene and protein expression, respectively. For in vivo studies, newly formed tissue was assessed by Masson's trichrome and von Kossa staining. Data indicated that TGF-β1 inhibited DPSCs proliferation in a concentration-and time-dependent manner (p<0.05) and induced cell cycle arrest but did not affect apoptosis. ALP activity was enhanced, while ARS reduced gradually with increasing TGF-β1 concentrations, accompanied by increased expression of early marker genes of odonto-/osteo-genic differentiation and decreased expression of late-stage mineralization marker genes (p<0.05). ALP expression was elevated in the TGF-β1-treatment group until 14 days, and the intensity of ARS staining was attenuated at days 14 and 21 (p<0.05). Compared with the control group, abundant collagen but no mineralized tissues were observed in the TGF-β1-treatment group in vivo. Overall, these findings indicate that TGF-β1 promotes odontogenic differentiation of DPSCs at early-stage while inhibiting later-stage mineralization processes.